TOWARDS CREATIVE TOOLS FOR PROMOTING BLOOD DONATION: THE CASE OF PUBLIC HEALTH IN MOROCCO - EL AMRANI LAMIAE; BENBBA BRAHIM; MOHAMMED NAJIB EL OUALIDI (Revue Marocaine de Recherche en Management et Marketing, 2017)
Attraction factors of Blood transfusion centre analysis is paramount however, the donor’s profile cannot be neglected. Therefore, 2 goals can be mentioned: